The impact of financial risks on the performance of Islamic Banks in Malaysia / Mohd Adib Adam Patarai and Nur Fakhira Mohamad Fauzi - Patarai, Mohd Adib Adam; Mohamad Fauzi, Nur Fakhira (Faculty of Business and Management, 2016)
The purpose of this study is to analyze the impact of financial on the performance of Islamic Banks in Malaysia from period. This study covers most of Islamic banking institutions in Malaysia which operated during period of 2008 to 2014. By using a panel data series, the data for 15 Islamic banks are taken from the Bank Scope database. There are several factors that have significantly effect on Islamic banks performance. One of them is financial risk. Financial risks that used in this study are credit risk, liquidity risk, operational risk, and capital risk. Overall result, the study finds significant relationship between capital risk, operational risk and financial performance. But there is no relationship between credit risk and liquidity risk towards performance of Islamic banks in Malaysia